A review on the future of work: online labour exchanges, or ‘crowdsourcing’: implications for occupational safety and health (Bilbao, 2015)
"The development of technology has expanded the possibility for ‘relocating’ work out of a traditional workplaces and entirely new forms of work organisation have emerged. Crowdsourcing — paid work organised through online labour exchanges — is one of these new work patterns. This article describes the main risks that can result from the vast range of tasks carried out by crowd workers. The rapid growth of this area of work has also created considerable challenges, and some examples of unresolved issues are discussed."